Triploidy in a sexually dimorphic passerine provides new evidence for the effect of the W chromosome on secondary sexual traits in birds - Camargo, Crisley de [UNESP]; Lisle Gibbs, H.; Costa, Mariellen C.; Silveira, Luis F.; Rainho, Claudia A. [UNESP]; Ribolla, Paulo E. M. [UNESP]; Wasko, Adriane P. [UNESP]; Francisco, Mercival R. (Wiley-Blackwell, 2017)
In birds, there are two main models for the determination of sex: the Z Dosage' model in which the number, or dose, of Z chromosomes determines sex, and the Dominant W' model which argues that a specific gene in the W chromosome may influence Z gene expression and determine sex. The best evidence for W determination of sex comes from birds with 2 copies of the Z chromosome paired with a single W (e.g. ZZW) which are nonetheless females. Here, we expand the species where such a mechanism may operate by reporting a case of a triploid Neotropical passerine bird with sexually dimorphic plumage, the SAo Paulo marsh antwren Formicivora paludicola. Evidence from 17 autosomal unlinked microsatellite loci, and CHD1 sex-linked locus, indicate that this individual is a 3n ZZW triploid with intermediate plumage pattern. This example expands our knowledge of sex determination mechanisms in birds by demonstrating that both the W and the two Z chromosomes affect the expression of morphological secondary sexual traits in a non-galliform bird.